Antipneumococcal Seroprotection Years After Vaccination in Allogeneic Hematopoietic Cell Transplant Recipients. (4th December 2019) - Robin, Christine; Bahuaud, Mathilde; Redjoul, Rabah; Jeljeli, Mohamed; Leclerc, Mathieu; Cabanne, Ludovic; Beckerich, Florence; Pautas, Cécile; Maury, Sébastien; Cordonnier, Catherine
Abstract: Background: International guidelines recommend vaccinating allogeneic hematopoietic cell transplant (HCT) recipients at 3 months after transplant, giving 3 doses of pneumococcal conjugate vaccine (PCV) followed by either a dose of 23-valent pneumococcal polysaccharide vaccine (PSV23) or a fourth PCV dose in the case of graft-versus-host disease (GvHD). However, the long-term immunity after this regimen is unknown, and there is no recommendation from 24 months after transplant regarding boosts. Our objective was to assess the antipneumococcal antibody titers and seroprotection rates of allogeneic HCT recipients years after different schedules of vaccination. Methods: We assessed 100 adult HCT recipients a median of 9.3 years (range: 1.7–40) after transplant. All patients had received at least one dose of PCV and were assessed for antipneumococcal immunoglobulin G (IgG) antibody titers against the 7 serotypes shared by PCV7, PCV13, and PSV23. Sixty-six percent of the patients had been vaccinated according to the current guidelines. Results: Considering an IgG titer ≥ 0.35 µg/mL as protective for each serotype, the seroprotection rate was 50% for 7/7 serotypes and 70% for 5/7 serotypes, with no differences between the different vaccination schedules. The lack of seroprotection was associated with a transplant performed not in complete remission or from a cord-blood unit, a relapse after transplant, or chronic GvHD at assessment. Conclusion: Because only half of the vaccinated patients had long-term protection, pending prospective studies defining the best boost program after the initial one, we recommend the assessment of specific IgG titers starting from 24 months to decide for further doses. Abstract : A median of 9 years after allogeneic hematopoietic stem cell transplant (HCT), only half of the recipients vaccinated against Streptococcus pneumoniae according to current guidelines are seroprotected. We recommend to assess the antipneumococcal IgG titers against the vaccine serotypes from 24 months to decide about boosts.